Short-Term Prognostic Model for Non-Traumatic Intracerebral Hemorrhage Patients: A Combination of Four Score, FUNC Score, and ICH Score - Saragih, Nurvira Annisa; Alfansuri Kadri; Chairil Amin Batubara (CoinReads Media Prima, 2024)
Introduction: Currently, the Functional Outcome in Patients With Primary Intracerebral Hemorrhage (FUNC) score, Full Outline of UnResponsiveness (FOUR) score, and Intracerebral Hemorrhage (ICH) score are utilized to predict outcomes in non-traumatic intracerebral hemorrhage (ICH) patients. The high mortality rate in non-traumatic ICH patients emphasizes the importance of scoring systems as predictive models for mortality prognosis. The aim of this study was to determine a short-term prognostic model for non-traumatic ICH patients by combining FUNC score, FOUR score, and ICH score. Method: This observational cohort study took place at the neurology ward and Intensive Care Unit of RSUP H. Adam Malik – Medan, from March to September 2023. Subjects meeting the study criteria were observed for 30 days to assess short-term outcomes (mortality). Multivariate logistic regression analysis was then conducted for the combined scores. Results: Significant effects were found between FUNC score, FOUR score, and ICH score on short-term mortality in non-traumatic ICH patients, each with a p-value < 0.001. However, the multivariate logistic regression analysis yielded statistically non-significant results (p > 0.05). Conclusion: While FUNC, FOUR, and ICH scores individually show a significant correlation with short-term mortality in non-traumatic ICH patients, their combination is ineffective for predicting mortality in this group.